Pendampingan Perencanaan Keuangan Demi Kemandirian Finansial di Masa Tua - Adilla, Tanaya; Yani, Ahmad; Srihastuti, Eni (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2024)
Financial planning before retirement is a crucial aspect of preparing for a secure and comfortable retirement. Bank Syariah Indonesia offers the BSI Pra Pensiun Berkah product as a financial solution for customers approaching the retirement phase. This community service activity aims to educate the public, particularly BSI customers, on the importance of pre-retirement financial planning. The method used in this service is service learning and was carried out at Bank Syariah Indonesia KCP Kediri Gudang Garam. The results of the service show that through this financial assistance, the program not only provides beneficial financial solutions but also enhances customers' understanding of the importance of financial literacy and sound retirement planning. Customers and prospective customers are very enthusiastic about participating in the socialization, and some are interested in registering.